Figurative language in biblical prose narrative : metaphor in the book of Samuel - Weiss, Andrea L. (Supplements to Vetus Testamentum, 2006)
This study applies several linguistic approaches to the book of Samuel in order to investigate the defining features of metaphor and the way metaphor and other forms of figurative language operate in biblical narrative. The book begins with an exploration of how to identify and interpret the metaphors in 1 Samuel 25. Next, the metaphors in 2 Samuel 16:16-17:14 are compared with other tropes, primarily metonymy and simile. Then the notion of "dead" metaphors is challenged while examining the figurative language in 1 Samuel 24. An in-depth analysis of the figurative language in these texts results in a better understanding of the mechanics of metaphor, and a richer, more nuanced reading of these stories, their characters, and language.